[Buildings] - (:unkn) unknown (My University, 2010)
Exterior view of a building, which might have been one of the buildings at the Leper Colony, Chacachacare Island, Trinidad. It is surrounded by undulating land and trees.
Colour: Sephia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Buildings--Trinidad and Tobago